Pelestarian Kearifan Lokal melalui Sekujang: Pengabdian Mahasiswa KKN UIN Fatmawati Sukarno Bengkulu di Desa Simpang: Pengabdian - Sidiq Nopal; Kaka Kiki; Bunga Bely; ⁠Yuni Nova; Fely Asry; Aprina Puspita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Local wisdom is a cultural heritage that reflects the social, spiritual, and moral values ​​of a community. The Sekujang tradition in Simpang Village, Seluma Regency, Bengkulu is one form of local wisdom of the Serawai community which is manifested in the practice of mutual cooperation and oral literary expressions in the form of pantun and traditional songs. However, this tradition has declined due to the flow of modernization and the decreasing involvement of the younger generation. This study aims to describe efforts to preserve the Sekujang tradition through the Real Work Lecture (KKN) program of students at the Fatmawati Sukarno State Islamic University of Bengkulu in 2025. With a qualitative participatory approach, data were obtained through observation, in-depth interviews, and visual documentation. The results of the study showed that student involvement in documenting traditions, educating youth, and organizing cultural performances collaboratively succeeded in rekindling community interest in local traditions. This activity not only strengthens the cultural identity of the community but also becomes a contextual learning medium for students. This study recommends the need for a cultural preservation program based on education and community participation in a sustainable manner.